2021
DOI: 10.7759/cureus.19791
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Factors in Predicting Mortality Among COVID-19 RT-PCR Positive Patients: A Retrospective Observational Study From a Tertiary Care Center

Abstract: Background: In coronavirus disease 2019 (COVID-19) patients, risk stratification based on clinical presentation, co-morbid illness, and combined laboratory parameters is essential to provide an adequate, timely intervention based on an individual’s conditions to prevent mortality among cases. Methods: A retrospective observational study was carried out from June to October 2020, including all reverse transcription-polymerase chain reaction (RT-PCR) positive COVID-19 non-survivors and control group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…A case study conducted in Malaysia also highlighted the profound impact of Covid-19 on mental health and general well-being [41]. In our study, the high fibrinogen ratio and low lymphocyte level trigger mortality is consistent with previous studies [40], [42].…”
Section: A Pre-modelingsupporting
confidence: 91%
“…A case study conducted in Malaysia also highlighted the profound impact of Covid-19 on mental health and general well-being [41]. In our study, the high fibrinogen ratio and low lymphocyte level trigger mortality is consistent with previous studies [40], [42].…”
Section: A Pre-modelingsupporting
confidence: 91%
“…On the other hand, in a Korean study of more than 5000 patients with COVID-19, logistic regression analyses showed that male sex and older age increased the risk of oxygen therapy requirements during hospitalization [ 42 ], similar to the findings in our study. A recent analysis from one of the Indian tertiary centers revealed that patients with SARS-CoV-2 infection who died in the course of the disease received high flow nasal cannula oxygen nearly four times more often than survivors [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several clinical, laboratory and radiological investigations that can predict the severity of disease and outcome in COVID-19 patients assigned to respiratory complications [ 12 ]. The vast majority of studies on neurological complications, including meta-analyses, focus on the kind of neurological complication and the outcome, while predictors of neurological sequelae are underexplored [ 13 , 14 ], but there are hardly any relevant predictors for neurological sequelae.…”
Section: Introductionmentioning
confidence: 99%